CONCEPTUAL FOUNDATIONS OF LINGUISTIC IDENTITY AND THE RELATIONSHIP BETWEEN THE INDIVIDUAL AND SOCIETY IN THE THOUGHT OF THE 20TH CENTURY (Scientific journal of the Fergana State University, 2026)
Within the anthropocentric trends of 20th-century linguistic science, this study examines the stages of the theoretical development of the concept of “linguistic personality”, as well as its individual and social aspects. The research analyzes the interconnections between the concepts of linguistic personality and symphonic personality developed by L. Weisgerber, N. S. Trubetzkoy, and V. V. Vinogradov, as well as their influence on modern linguistics. Furthermore, the study emphasizes the role of subsequent works by G. I. Bogin and Yu. N. Karaulov in enriching the concept of linguistic identity with cognitive foundations. By integrating the philosophical, psychological, and linguistic foundations of the theory of linguistic identity, the paper substantiates the unity between the individual idiolect and collective linguistic experience.